Salinomycin: A new paradigm in cancer therapy - Jayant Dewangan; Sonal Srivastava; Srikanta Kumar Rath (Tumor Biology, 2017)
The primary hurdle in the treatment of cancer is acquisition of resistance by the tumor cells toward multiple drugs and selectively targeting the cancer stem cells. This problem was overcome by the chemotherapeutic property of recently discovered drug salinomycin. Exact mechanism of action of salinomycin is not yet known, but there are multiple pathways by which salinomycin inhibits tumor growth. Salinomycin decreases the expression of adenosine triphosphate–binding cassette transporter in multidrug resistance cells and interferes with Akt signaling pathway, Wnt/β-catenin, Hedgehog, and Notch pathways of cancer progression. Salinomycin selectively targets cancer stem cells. The potential of salinomycin to eliminate both cancer stem cells and therapy-resistant cancer cells may characterize the compound as a novel and an efficient chemotherapeutic drug.